WATER'S FLOW OF PEACE - VENTURI, LUIS ANTONIO BITTAR (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This book presents the results of research cooperation between the Departments of Geography of the University of São Paulo, the University of Damascus and the University of Cambridge. It serves to refute the widely spread Malthusian paradigm--which forecasts conflicts due to water scarcity--by showing that this perspective has neither an empirical nor conceptual basis. It begins from the hypothesis that both sharing water politics and the use of technology can annul the water scarcity-conflict paradigm. To corroborate this hypothesis, the book uses two variables illustrated by two contexts: th.